The analysis of last year junior high school students’ scientific literacy in biology topics - Rezky Nefianthi; Muhammad Novaldy Nur Dwinanda Wahab (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
The urgency of this study lies in the importance of science literacy assessment to reflect the quality of the learning process, especially in biology topics that require laboratory skills related to science literacy. This study used a quantitative descriptive analysis approach to analyze and compare the level of science literacy of junior high school students in biology topics. The assessment tool in this study was developed based on PISA indicators to measure students' science literacy. Data collection was conducted using purposive sampling technique to obtain samples from two different junior high schools. Based on the results of the study of 134 students from two classes in each school, it was found that 113 students still had below average science literacy skills, while only 21 students were above average. Students with above-average scores were at levels 5 and 6, while students with below-average scores were at levels 2, 3, and 4. This study shows that there needs to be special attention from teachers to focus more on developing students' science literacy. The scientific implication in the future is to improve the quality of the learning process to develop students' science literacy, especially on the topic of biology.Abstrak. Urgensi penelitian ini terletak pada pentingnya penilaian literasi sains untuk mencerminkan kualitas proses pembelajaran, khususnya pada topik biologi yang membutuhkan keterampilan laboratorium terkait literasi sains. Penelitian ini menggunakan pendekatan analisis deskriptif kuantitatif untuk menganalisis dan membandingkan tingkat literasi sains siswa SMP dalam topik biologi. Alat penilaian dalam penelitian ini dikembangkan berdasarkan indikator PISA untuk mengukur literasi sains siswa. Pengumpulan data dilakukan dengan teknik purposive sampling untuk memperoleh sampel dari dua SMP yang berbeda. Berdasarkan hasil penelitian terhadap 134 siswa dari dua kelas di setiap sekolah, ditemukan bahwa 113 siswa masih memiliki keterampilan literasi sains di bawah rata-rata, sementara hanya 21 siswa yang berada di atas rata-rata. Siswa dengan nilai di atas rata-rata berada pada level 5 dan 6, sedangkan siswa dengan nilai di bawah rata-rata berada pada level 2, 3, dan 4. Penelitian ini menunjukkan bahwa perlu adanya perhatian khusus dari guru untuk lebih fokus pada pengembangan literasi sains siswa. Implikasi ilmiah di masa mendatang adalah peningkatan kualitas proses pembelajaran guna mengembangkan literasi sains siswa, khususnya pada topik biologi.